Large increase of the anisotropy factor in the overdoped region of Ba(Fe1-xNix)2As2 as probed by fluctuation spectroscopy. (18th May 2015) - Ramos-Álvarez, A; Mosqueira, J; Vidal, F; Lu, Xingye; Luo, Huiqian
Abstract: We study the diamagnetism induced by thermal fluctuations above the superconducting transition of the iron pnictide Ba(Fe Ni x )2 As2 with different doping levels. The measurements are performed with magnetic fields up to 7 T applied in the two main crystal directions. These data provide double information: first, they confirm at a quantitative level the applicability to these materials of a 3D-anisotropic Ginzburg–Landau approach valid in the finite field regime. Then, they allow us to determine the doping-level dependence of the in-plane coherence length and of the superconducting anisotropy factor, γ . Our results provide a stringent confirmation of the large increase of γ with the doping level, as recently proposed from magnetoresistivity measurements. The implications of the applicability of the model used to a multiband superconductor are discussed.